Development of a Tourism Awareness Index and Its Determinants among Tourism Workers - Sarni Maniar Berliana; Krismanti Tri Wahyuni; Victoria P. Valenzuela; Joshua G. Meneses; Wahyuni Andriana Sofa; Maria A. Hasiholan Siallagan; Ditto Satrio Wicaksono (UIN Sumatera Utara, 2026)
Tourism worker awareness is essential for service quality and sustainable tourism development, yet a validated composite measure remains lacking. This study develops the Tourism Awareness Index (TAI) based on the Sapta Pesona framework using survey data from 868 tourism workers in Malang Regency, Indonesia. Six dimensions showed satisfactory internal consistency (Cronbach's alpha = 0.65-0.81), while one dimension had alpha slightly above 0.60. Factor analysis with principal component extraction identified a three-factor structure explaining 74.2% of total variance, supported by a KMO value of 0.91 and a significant Bartlett's test. Ordered logistic regression revealed that workers aged 45 years and above (OR = 1.42, p = 0.042) and those with at least a high school education (OR = 1.60, p = 0.004) were more likely to achieve higher TAI levels, while lack of foreign language proficiency reduced this likelihood (OR = 0.57, p = 0.003). The TAI offers a statistically validated tool and may support workforce development and tourism policy.